Quick Reference Guide to Foliar Fungicides - Jamie D. Burrow; Megan M. Dewdney (EDIS)
This 2-page reference guide provides quick access to foliar fungicide recommendations from the Florida Citrus Production Guide. Also included are guidelines for fungicide resistance management. It is a minor revision written by Megan M. Dewdney and published by the Plant Pathology Department, July 2019.